2020
DOI: 10.14449/jbd.2020.8.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study for Clinical Outcomes of Triple-Positive and Triple-Negative Breast Cancer: Long-term Results in 161 Patients Followed in a Single Center

Abstract: Purpose: Triple negative breast cancer (TNBC) is one of the most aggressive subtypes of breast cancer. However, we have often experienced that triple positive breast cancer (TPBC) shows more aggressive clinical features than TNBC. In this retrospective study, we aimed to examine the differences in clinical courses between TNBC and TPBC. Methods: Using medical records and clinical data, we selected patients with breast cancer who met the criteria for the two groups, TNBC and TPBC, based on the expression or abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In this study, multivariate analyses showed that chemotherapy was not a significant prognostic factor. In addition, the presence of LVI was related to poor prognosis, and this result has further been reported in other studies [14,17,23,24]. Therefore, more intensive treatment should be considered for TNBC patients with LVI.…”
Section: Discussionsupporting
confidence: 74%
“…In this study, multivariate analyses showed that chemotherapy was not a significant prognostic factor. In addition, the presence of LVI was related to poor prognosis, and this result has further been reported in other studies [14,17,23,24]. Therefore, more intensive treatment should be considered for TNBC patients with LVI.…”
Section: Discussionsupporting
confidence: 74%
“…Patients with S100A4-positive tumors have inferior metastasis-free and overall survival compared to S100A4-negative. S100A4-expression was strongly associated with triple-negative subtype, metastasis-free and overall survival was numerically reduced in patients with S100A4-positive tumors [ 5 ]. However, sometimes TPBC shows more aggressive clinical features than TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypic or phenotypic heterogeneity of breast cancer is diverse. While triple-negative breast cancer generally has the most aggressive behavior and poor clinical outcomes [ 18 , 19 , 20 ], triple-positive breast cancer has also been found to exhibit aggressive behavior, despite the availability of antibody-targeted therapy or chemotherapy [ 21 ].…”
Section: Introductionmentioning
confidence: 99%